AMELIORATIVE ROLE OF SILYMARIN AGAINST ASPARTAME–INDUCED BIOCHEMICAL CHANGES, OXIDATIVE STRESS, INFLAMMATORY EFFECT AND GENOTOXICITY IN MALE ALBINO RATS - ELBALLAT, SABHA E.; ABAS, AL-SHIMAA M. (International Journal of Current Pharmaceutical Research, 2020)
Objective: Aspartame (ASP) is one of the most common artificial sweeteners. It has been recorded to be safe by World Health Organization. However, numerous publications have concluded that ASP is a genotoxic and carcinogenic sweetener. Methods: The current study aims to examine the effect of ASP consumption (250 mg/kg body weight/day for 90 d) on some biochemical parameters, oxidative/antioxidative status in different tissues, Tumor Necrosis Factor-α (TNF-α), chromosomal aberration (CA) frequency and mitotic index (MI) percentage in addition to the possible ameliorative role of silymarin (50 mg/kg body weight/day for 90 d) against ASP-induced toxicity in male albino rats. Results: The present results have confirmed that ASP is able to induce significant increase in the blood glucose level, liver, kidney and lipid function tests, Malondialdehyde (MDA) level, serum TNF-α level, frequency of CA and MI%. Meanwhile, Glutathione reduced level (GSH), Glutathione–S-transferase (GST) and catalase activity (CAT) were decreased by ASPadministration. Recovery group showed slight enhancement in all parameters but remained significant as compared to the control group. Co-administration of ASP with silymarin showed greater improvement than the recovery group. Conclusion: Silymarin have an ameliorative role against biochemical oxidative stress, inflammatory changes in blood and different tissues, chromosomal aberrations and MI% induced by ASP administration.